TOGETHER Model: A Participatory Student- Development Model in Multicultural Society for Thailand’s Deep South University Network - Kadem, Yutthana; Jai-aree, Apichart; Tanpichai, Prasong (Asian Interdisciplinary and Sustainability Review, 2019)
The purpose of this qualitative research study was to synthesize an integrated studentdevelopment model in multicultural society for Thailand’s deep south university network. Data collection was conducted through brainstorming, group discussion, critique meeting, and subsequent forum for data return and opinion sharing. The 45 key informants included 8 higher-education institutional presidents from the three southern-border provinces, 7 studentdevelopment practitioners, 20 student leaders, 5 alumni representatives, and 5 civil-society representatives. The derived data were used in a content analysis logical based on related concepts, theories, and research studies. TOGETHER Model, a participatory studentdevelopment model, was operated under TDSUN Network which is an integrated studentdevelopment network in multicultural society for Thailand’s deep south university network. The findings revealed that the model covered 6 following activity areas: 1) academic; 2) sports and recreation; 3) promotion of Thai culture; 4) community service and environmental protection; 5) exchange programs for students and student-development practitioners; and 6) knowledge enhancement. The results of this study were found fruitful to the participatory student development as they fostered an integration of student activities which was in line with the concepts of peace building and multicultural society of the three southern-border provinces.